2006
DOI: 10.1088/0022-3727/39/10/002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal annealing on Fe40Ni38B18Mo4thin films: modified Herzer model for magnetic evolution

Abstract: Magnetic properties of nano-crystalline soft magnetic alloys have usually been correlated to structural evolution with heat treatment. However, literature reports pertaining to the study of nano-crystalline thin films are less abundant. Thin films of Fe 40 Ni 38 B 18 Mo 4 were deposited on glass substrates under a high vacuum of ≈ 10 −6 Torr by employing resistive heating. They were annealed at various temperatures ranging from 373 to 773 K based on differential scanning calorimetric studies carried out on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…As a result of higher oxidation of the film, the saturation magnetization is further reduced. Earlier studies by Hysen et al [19] and Senoy et al [20] on the annealing effects of FeNiMoB thin films by thermal evaporation showed that Mo and B were not present in the film. The Fe Ni phase precipitated on annealing, resulting in a nanocrystalline structure exhibiting high saturation magnetization.…”
Section: Magnetic Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…As a result of higher oxidation of the film, the saturation magnetization is further reduced. Earlier studies by Hysen et al [19] and Senoy et al [20] on the annealing effects of FeNiMoB thin films by thermal evaporation showed that Mo and B were not present in the film. The Fe Ni phase precipitated on annealing, resulting in a nanocrystalline structure exhibiting high saturation magnetization.…”
Section: Magnetic Studiesmentioning
confidence: 95%
“…Compared to the bulk FeNiMoB ribbons, the films show a low value of saturation magnetization. Hysen et al [19] have reported a saturation magnetization of 70 emu g −1 for annealed films of Fe-Ni. In this investigation we obtained a very low value of saturation magnetization for the annealed film.…”
Section: Magnetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vapour deposition offers a simple alternative to sputter deposition in obtaining thin films of supersaturated solid solutions and other metastable states. Some attempts to prepare Metglas 2826 MB thin films by thermal evaporation have been reported in the literature [10][11][12][13][14][15]. Thin films of Fe 40 Ni 38 Mo 4 B 18 were prepared by the flash evaporation technique [10].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic studies were not carried out on these samples and the main focus of the paper was on the structural evolution of these films with thermal annealing. An alloy film deposited from a target of composition Fe 40 Ni 38 Mo 4 B 18 was studied previously by our group [11][12][13][14][15]. When Metglas thin films are grown it is necessary that their composition is determined as accurately as possible and technique like XPS is very useful in such studies.…”
Section: Introductionmentioning
confidence: 99%